The most common genes involved in epigenetics modifications among Iranian patients with breast cancer: A systematic review - Iranshahi, N.; Zafari, P.; Yari, KH.; Alizadeh, E. (Cellular and Molecular Biology, 2016)
Breast cancer, with a lifelong risk of one in nine, is the most common cancer among women. In Iran, breast cancer is one of the growing and important women's health problems. Several environmental, genetic and epigenetics factors have been suggested to have a role in breast cancer development. Epigenetics alterations are heritable changes in gene expression that occur without causing any change in DNA sequence. DNA methylation as a main epigenetics modification in human cancer is found as a promising biomarker in early detection of breast cancer. Association between epigenetics changes of many gene promoters with the risk of breast cancer has been investigated worldwide. This aberrant methylation may be occur in specific genes related to cell cycle, cell adhesion, apoptosis and DNA repairing mechanisms and results in silencing of these important genes. In this review study, we have gathered all the data until December 2015 about epigenetics modifications among Iranian population with breast cancer.  We searched international web databases such as: PubMed, Scopus, and Persian web databases; IranMedex and Magiran to investigate the association of epigenetics change and incidence of breast cancer among Iranian population. Using "methylation” or "epigenetics” key words and "Iran” as affiliation, all the published data were 31. After arbitrary limitation in search keywords the result have been 20 articles.  Data analysis show that "ER-Î±” and "E-Cadherin” are most common studied genes in epigenetics modifications. Also, maximum studies were done in Tehran and Tabriz. We thought that more studies will be helpful to reveal the relation of methylation status in candidate genes with the breast cancer risk in Iranian populations.